2022
DOI: 10.1093/bbb/zbac081
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue distribution of orally administrated imidazole dipeptides in carnosine synthase gene knockout mice

Abstract: Imidazole dipeptides (ID) are abundant in skeletal muscle and the brain and have various functions, such as antioxidant, pH-buffering, metal-ion chelation. However, the physiological significance of ID has not been fully elucidated. In this study, we orally administered ID to conventional carnosine synthase gene-deficient mice (Carns-KO mice) to investigate the pharmacokinetics. Carnosine or anserine was administered at a dose of 500 mg (approximately 2 mmol) per kilogram of mouse body weight, and ID contents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is reported that, in general, bonito, bigeye tuna, and southern tuna contain about 1070 mg, 1260 mg and 636 mg of anserine per 100 g of fish flesh, respectively [ 17 ]. We learned that the doses of anserine used in previous animal experiments ranged from 2 mg/kg·bw to 80 mg/kg·bw [ 18 , 19 ], so we chose the 1 mg/10 mg/100 mg kg·bw as the low/medium/high doses of anserine intervention in our experiment. Our results did show that medium doses of anserine were the most effective in improving hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that, in general, bonito, bigeye tuna, and southern tuna contain about 1070 mg, 1260 mg and 636 mg of anserine per 100 g of fish flesh, respectively [ 17 ]. We learned that the doses of anserine used in previous animal experiments ranged from 2 mg/kg·bw to 80 mg/kg·bw [ 18 , 19 ], so we chose the 1 mg/10 mg/100 mg kg·bw as the low/medium/high doses of anserine intervention in our experiment. Our results did show that medium doses of anserine were the most effective in improving hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
“…Carnosine is provided by nutrition and tissue carnosine synthase (Carns1), but the impact of the latter is uncertain. In Carns1-KO mice, brain and muscle are carnosine-deficient, and stores can be replenished by oral intake [44], but the Carns1-KO had no impact on kidney and brain markers of carbonyl and oxidative stress in healthy and diabetic mice [45]. In contrast, anserine and carnosine are rapidly degraded by CN1, and kidney tissue CN1 activity in healthy and in type 2 diabetic mice is correlated with kidney anserine and carnosine concentrations and the tissue carbonyl and oxidative stress level [46].…”
Section: Discussionmentioning
confidence: 99%
“…Following the method described by Sakano et al [ 17 ], plasma free amino acid (arginine, lysine, methionine, isoleucine, leucine, valine, phenylalanine, threonine, tryptophan, histidine, glycine, glutamic acid, glutamine, aspartic acid, serine, alanine, cysteine, tyrosine, proline, taurine, N π -methylhistidine, and N τ -methylhistidine) concentrations were determined using a fully automated amino acid analyzer (JLC-500/V2, Japan Electron Optics Laboratory, Tokyo, Japan) after plasma samples were deproteinized with 3% sulfosalicylic acid solution.…”
Section: Methodsmentioning
confidence: 99%